Do mirror movements relate to hand function and timing of the brain lesion in children with unilateral cerebral palsy?. (8th December 2015) - Klingels, Katrijn; Jaspers, Ellen; Staudt, Martin; Guzzetta, Andrea; Mailleux, Lisa; Ortibus, Els; Feys, Hilde
Abstract : Aim: This study aimed to systematically map the severity of mirror movements in both hands in a prospective cohort of children with unilateral cerebral palsy, and to explore the relationship with hand function and brain lesion type. Method: Seventy‐eight children were included (41 males, 37 females; age 9y 4mo, SD 3y 1mo, range 5–15y). Mirror movements were scored during three repetitive tasks following Woods and Teuber criteria. Strength, tone, Melbourne Assessment, Jebsen–Taylor test, and Assisting Hand Assessment were evaluated. Lesions were classified into malformations ( n =5), periventricular ( n =43), cortico–subcortical ( n =22), and postnatally acquired lesions ( n =8). Results: Significantly more mirror movements were observed in the non‐paretic versus the paretic hand ( p ≤0.003). Higher mirror movement scores in the non‐paretic hand significantly correlated with lower distal strength and lower scores on unimanual and bimanual assessments ( r =0.29–0.41). In the paretic hand, significant differences were found between lesion types ( p =0.03). Interpretation: The occurrence of mirror movements in the non‐paretic hand seems related to hand function while mirror movements in the paretic hand seem more related to the lesion timing, whereby children with earlier lesions present with more mirror movements. What this paper adds: More mirror movements are observed in the non‐paretic versus the paretic hand. Poor hand function correlates with more mirror movements in the non‐paretic hand. Mirror movements in the paretic hand are related to the brain lesion type. This article is commented on by Norton and Sawicka on pages655–656 of this issue.